International Tax Competition and the Deficit Bias - Calin Arcaelan (Center for Economic Studies and ifo Institute (CESifo), 2015)
I analyze the dynamic effects of tax competition on public budget deficits. I find that stronger tax competition leads to a fiscal deficit bias at the early stages of financial liberalization. When countries differ in terms of capital mobility, further liberalization leads to external imbalances and diverging fiscal deficits while corporate tax rates converge. Consistent with theory, I find that stronger tax competition increases deficits in a sample of OECD countries, controlling for tax revenues and other standard determinants of fiscal deficits.
Keywords: E62; F62; 330; international tax competition; political economy; deficit bias; redistribution